2014
DOI: 10.1111/ahe.12102
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Thoracic Vascularization in Some Deer Species: Pampas Deer (Ozotoceros bezoarticus), Brown Brocket Deer (Mazama gouazoubira) and Axis Deer (Axis axis)

Abstract: In this study, the arterial distributions of the aortic arches of three deer species (Axis axis, Ozotoceros bezoarticus and Mazama gouazoubira) were described. The animals were dissected immediately after being found dead. Latex injection method was used to observe the vascularization of the thorax. The branching pattern of the arteries of the thoracic aorta in O. bezoarticus was similar to domestic ruminants. In the M. gouazoubira and A. axis, there were no bicarotid trunk. Interestingly, the first branch of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The SB in type CIII in this study also branches off the CCT, IT, and SC in that order and the pattern is symmetrical on the left and right [9]. The AA and BC branching patterns and order of the IT and SC of the Siberian roe deer in this study are similar to those of other ruminants, but the BC differs from those of the buffalo [5, 23], Korean water deer [1], brown brocket deer [21] and axis deer [21], which do not have that artery. Siberian roe deer differ from the Korean native goat [18] in that the SC branches from the SB before the IT.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…The SB in type CIII in this study also branches off the CCT, IT, and SC in that order and the pattern is symmetrical on the left and right [9]. The AA and BC branching patterns and order of the IT and SC of the Siberian roe deer in this study are similar to those of other ruminants, but the BC differs from those of the buffalo [5, 23], Korean water deer [1], brown brocket deer [21] and axis deer [21], which do not have that artery. Siberian roe deer differ from the Korean native goat [18] in that the SC branches from the SB before the IT.…”
mentioning
confidence: 63%
“…Because a typical subtype was present on the right but not left side, the diversity was due not to the RCCT but to the LCCT branching sites. SB branch asymmetry was observed in 71.4% of cases, whereas symmetry was only seen in 28.6%, which differs from domestic ruminants [9] and the brown brocket deer [21]. Patterns such as subtype I could be unique to Siberian roe deer since other studies on deer [1, 21] and domestic ruminants [9, 18] have not reported this pattern.…”
mentioning
confidence: 96%
See 3 more Smart Citations